A visual graphic tool to support the production of simple sentence structures in a student with learning disability - Valiquette, Christine; Gérin-Lajoie, Anne-Marie; Sutton, Ann (Child language teaching and therapy, 2006)
A tool was devised to improve spoken syntax through manipulation of graphic symbols. The participant, a French-speaking 11-year-old girl with general learning disability, learned to produce subject-verb-object (SVOn) sentences and transform them into a subject-object-verb (SOpV) structure in which the object becomes pronominal in a preverbal position. The production of personal pronouns in subject position was also targeted. Didactic methods were selected and administered for a total of 12 individual sessions. Pre-and post-measurements in an elicitation task (picture description) and language sample analysis showed significant improvement on target productions.